2005
DOI: 10.4028/www.scientific.net/msf.475-479.1325
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Forming Technology in Gelcasting

Abstract: Controllable forming technology is one of the key problems for the industrial application of gelcasting. In order to solve this problem, various kinds of influence factors in gelcasting were investigated. Trace ions, ionic strength, pH, dispersant agent, premix, amount of initiator and catalyst, temperature, pressure, materials of container and inhibitor all have influence on solidification process of ceramic slurry. The forming process of gelcasting can be controlled effectively by adjusting these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…This process does not need the extra force and can realize an in-situ polymerization, which is beneficial for preparing the samples with high-quality, uniformity, and complex-shape. What is more, its polymerization time can be controlled by adjusting the amount of initiator and catalyst and the gelled green body has high strength so that the cost of machining is low [13][14][15][16]. Our preliminary research showed that the degree of texture could reach to 0.84 in SiC ceramics prepared in a low magnetic field of 6 T compared with other textured SiC prepared in 10 T or 12 T [8][9][10]17].…”
Section: Introductionmentioning
confidence: 77%
“…This process does not need the extra force and can realize an in-situ polymerization, which is beneficial for preparing the samples with high-quality, uniformity, and complex-shape. What is more, its polymerization time can be controlled by adjusting the amount of initiator and catalyst and the gelled green body has high strength so that the cost of machining is low [13][14][15][16]. Our preliminary research showed that the degree of texture could reach to 0.84 in SiC ceramics prepared in a low magnetic field of 6 T compared with other textured SiC prepared in 10 T or 12 T [8][9][10]17].…”
Section: Introductionmentioning
confidence: 77%
“…Before drying green gelcast bodies, the dipping pretreatment was applied, in which green gelcast bodies were soaked in a certain concentration of APS solution. The aim is to degrade the polymer; thereby, reticular macromolecular polymer chains (large molecules) are reduced to linear polymer chains (small molecules) 26,27 . Drying time versus linear shrinkage rate with different methods is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The aim is to degrade the polymer; thereby, reticular macromolecular polymer chains (large molecules) are reduced to linear polymer chains (small molecules). 26,27 Drying time versus linear shrinkage rate with different methods is shown in Fig. 7.…”
Section: ) Drying Of Gelcasting Partsmentioning
confidence: 99%
See 1 more Smart Citation
“…The forming ability is only limited by the complex degree of the mold cavity rather than mold material, many kinds of materials such as wax, plastics, resin, metal, etc. can be used (Dhara et al , 2002; Yang et al , 2005). Compared with injection molding, gelcasting green bodies have advantages of higher strength, better uniformity, lower organic content, easiness of degreasing and no defects such as warpage, cracking, etc.…”
Section: Introductionmentioning
confidence: 99%